PERAN UNITED NATIONS CHILDREN’S EMERGENCY FUND (UNICEF) DALAM MENANGGULANGI KRISIS KESEHATAN DI VENEZUELA TAHUN 2018-2019 - Renni Modita Putri; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research aim to describes the roles of the UNICEF (United Nations Children’s Emergency Funds) as non-governmental organization in tackling the health crisis in Venezuela in 2018-2019. UNICEF works in 190 countries in the entire world and territories to save children’s lives, to defend their right and to help them to fulfil their potential creativity from child through adolescenst in every condition such as victim of crisis, victim of conflict, victim of natural disaster.        UNICEF will help to save children’s lives. Since the Venezuelan crisis began in 2014, It has been affect the economic, politics and health system in Venezuela. The reason why health crisis in Venezuela rising is because of the hyperinflation and  the  collapse of health system and infrastructure and the lack of food stock, lack of medicine, lack of clean water dan lack of government’s participation makes Venezuelan suffering more difficult such as the collapse of infrastructure, malnutrition, epidemic of deaceses such as Malaria, Tuberculosis, HIV-AIDS.The research use pluralism perspective which believes that states are not the only actors in international world. This research also is guide by theory of international organizations role. The method of this research is qualitative method. The data collection incorporates by literature study from journals, books, documents and websites. This research shows the role by UNICEF in tackling the health crisis in Venezuela by excecuting programs that has been created for the people and child tjat affected by the health crisis and this research also explained the obstacles that UNICEF faced to help people lives specially children and pregnant woman suffer the health crisis. This research concludes programs in tackling health crisis in Venezuela which is UNICEF as motivator, UNICEF as communicator, UNICEF as mediatorKeywords :Role, UNICEF,Health Crisis, Collapse, Hiperinflation